Daya Terima Menu Sayur di Sebuah Asrama Pendidikan di Kota Semarang: Acceptance of Vegetable Menu at A Reformatory in Semarang - Puji Afiatna; Devinta Fitriani Rudin; Salisa Kinanti Nurul F; Ziana Andrian (JURNAL GIZI DAN KESEHATAN, 2023)
Reformatory is an institution that organizes food for its people. Students as residents of reformatory need to get quality food and contain balanced nutrients to meet their needs. Fulfillment of nutrients one of them is through vegetables. Vegetables are one of the menus served for boarding students and there are the most leftovers. The purpose of this study was to describe the acceptability of vegetable menus in educational dormitories in the city of Semarang. This research is a descriptive observational study with a cross sectional approach with a sample of 32 large bowls of vegetables and 172 respondents. The data collected were vegetable residues which were weighed with digital scales with an accuracy of 0.1 gram and vegetable preferences collected with a preference test questionnaire. The result was that 56.25% of the vegetables served were not consumed. 31.25% leftover vegetables >20% and 25% leftover vegetables <20%, 43.75% consumed. Acceptability of vegetables is 79.91% included in the enough category. Texture that is too overcook, taste and boredom in the vegetables served are related to poor acceptance. Training for processing staff is needed so that they process vegetables properly and modify vegetable recipes. ABSTRAK Asrama pendidikan merupakan institusi yang menyelenggarakan makanan untuk warganya. Siswa sebagai warga asrama pendidikan perlu mendapatkan makanan yang berkualitas dan mengandung zat gizi seimbang untuk memenuhi kebutuhannya. Pemenuhan zat gizi salah satunya adalah melalui sayur. Sayur menjadi salah satu menu yang disajikan untuk siswa asrama dan paling banyak terdapat sisa. Tujuan penelitian ini untuk mengetahui gambaran daya terima menu sayur di asrama pendidikan di Kota Semarang. Penelitian ini merupakan penelitian deskriptif observasional pendekatan cross sectional dengan sampel sebanyak 32 mangkuk besar sayur dan 172 responden. Data yang dikumpulkan adalah sisa sayur yang ditimbang dengan timbangan digital dengan ketelitian 0,1 gram dan kesukaan sayur yang dikumpulkan dengan kuesioner uji kesukaan. Diperoleh hasil bahwa 56,25% sayur yang disajikan tidak dihabiskan. 31,25% sisa sayur >20% dan 25% sayur sisa <20%, 43,75% habis dikonsumsi. Daya terima menu sayur adalah 79,91% termasuk dalam kategori cukup. Presentase terendah daya terima sayur ada pada aspek tekstur, yaitu 78,73%. Tekstur yang terlalu lunak (overcook), citarasa dan rasa bosan pada sayur yang disajikan berkaitan dengan kurang baiknya daya terima. Diperlukan pelatihan petugas pengolah agar dalam mengolah sayur dengan tepat dan modifikasi resep sayur.